From Classroom to Career Development Planning: Eportfolio Use Examples - Ana Coric Samardzija (International Journal of Emerging Technologies in Learning (iJET), 2014)
In this paper we will present several examples of different maturity levels of ePortfolio usage at the Faculty of Organization and Informatics, University of Zagreb, Croatia. Firstly, we will illustrate basic in-class uses of ePortfolio in which students are introduced with the ePortfolio concept, self-reflection, self-monitoring and knowledge management. The primary goal of this phase is to show students how to record, plan and improve their professional skills in order to facilitate their preparation for the labour market. This phase is also aimed at recording and showcasing of students’ work and self-assessment. The second example of ePortfolio usage in this paper concerns self-guidance monitoring at the postgraduate level, where it is used to monitor the activities and progress of PhD students as well as to simplify communication between supervisors and doctoral candidates. In addition, by using the ePortfolio pattern, doctoral students are encouraged to start planning their careers as scientific researchers and experts. Finally, we introduce an example of using ePortfolios for academic human resources management as part of institutional quality assurance. For that purpose, a career development plan was developed to collect and monitor the work and progress of academic staff (both young researchers and teaching assistants).